A social norms approach to substance abuse prevention in youth “the more i think you drink, the more i drink” - Sönmez, Ekin; Akvardar, Yıldız (Journal of Dependence, 2015)
The onset of alcohol and substance use in youth occurs generally under the influence of peers especially around the beginning of their time at university. Peers and normative beliefs play important roles in regard to healthy behaviours. The social norms approach, a noteable health improvement strategy in recent years, has provided both a theoretical framework for binge drinking and substance abuse and has formed a basis for practical application. According to this theory, the misconception that unhealthy behaviours or attitudes are more common than they are in reality leads to an increase in the prevalence of such behaviours and attitudes, whereas the presentation of the actual data reduces the prevalence of such behaviours. Social norms interventions have been shown to be effective among high school and university students. Social norms theory has potential for both setting an explanatory etiological model for alcohol and substance abuse and serving as a functional means of intervention in which young people can actively participate. With the help of appropriate media, such interventions can reduce frequent and excessive alcohol use, resulting in prevention of the development of disorders related to alcohol use. Therefore, proactive studies among students that aim to correct the misconceptions about social norms regarding alcohol and substance consumption should be supported.